Standardization, Antioxidant, and Antimicrobial Activity Test of Ethanol Extract from Andiroba Bark (Carapa guianensis) - Hasanuddin, Silviana; Isrul, Muhammad; Saafi, La Ode; Dewi, Citra; Yulianingsih, Eka Putri; Dewi, Shafira Endah Amartya; Nita, Waode Adisti Elmira; Zainal, Mardani (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Most degenerative diseases are linked to excess free radicals generated by the body's metabolism or exposure to external factors. Antioxidants are used to help neutralize free radicals and treat bacterial infections. Andiroba bark (Carapa guianensis) is one of the plants used empirically by the people of the Province of Jeneponto to treat various diseases. This study aims to determine whether the ethanol extract of andiroba bark meets the standardization requirements and exhibits antioxidant activity, and to identify its ability to inhibit the growth of Staphylococcus aureus, Propionibacterium acnes, Staphylococcus epidermidis, and Escherichia coli. The results of the research showed that the results of specific and non-specific standardization of the ethanol extract from andiroba bark met the specified requirements, the ethanol extract had an antioxidant activity with an IC50 value of 15.985 μg/mL, which was included in the group of very strong antioxidants and could inhibit the growth of Staphylococcus aureus, Propionibacterium acnes, Staphylococcus epidermidis, and Escherichia coli bacteria at concentrations of 0.01 g/mL, 0.05 g/mL, and 0.1 g/mL. Overall, the ethanol extract from andiroba bark meets the standardization requirements and exhibits antibacterial activity.